A REVIEW ARTICLE ON A PPLICATION OF PREBIOTICS IN AQUACULTURE (International Journal of Food and Nutritional Sciences, 2022)
Aquaculture productivity is increasing rapidly and it has been a exploding sector among all kind of aquatic food. To get economic profit, farmers uses several kinds of chemicals, drugs or antibiotics to increase the rate of production within a very small period of time. Because of these reasons; the aquatic environment of aquaculture is in loss. Not only that, the condition of water becomes poor. And by following this way, lots of disease arises in fish, affect the growth of fish and even several environmental stress condition appeared. Disease control in fish culture, rather aquaculture is more important to counter the economic losses as well as public health. Use of drugs, antibiotics and chemicals are old method to prevent disease. These type of method is not so much beneficial. So, new method is necessary to release these environmental stress and provide suitable environment for this culture. This review will present the effectiveness of application of pre and probiotics to improve better growth of fish, helps in growing beneficial bacteria and present infective bacteria.